2011
DOI: 10.1353/sel.2011.0018
|View full text |Cite
|
Sign up to set email alerts
|

Henry VIII, Shakespeare, and the Jacobean Royal Court

Abstract: Early Stuart history plays by William Shakespeare and Samuel Rowley join an ongoing debate over the continued cultural relevance of Henry VIII to the Stuart Court. In anachronistic representations of the Tudor king, both playwrights lodge typological arguments designed to flatter the perceived interests and agendas of their respective patrons, King James and Prince Henry Frederick. This evidence raises larger implications concerning the potential of Shakespearean-era plays to offer royal counsel and shape opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Mark Rankin has explored the mechanisms of offering counsel through these two Jacobean plays, and has observed that both Rowley and Shakespeare represented Henry VIII as 'a dynastic predecessor to Stuart rule'. 17 Shakespeare and Rowley framed this character's actions and utterances so as to appeal to the 'interests and agendas' of both James I and his son and heir Henry Frederick. 18 The performance of kingship onstage as a means of offering counsel or seeking royal favour has been extensively studied, 19 and in the context of Jacobean plays on early Tudor history any dramatic representation of the current monarch's predecessors is reflective of the current monarch rather than of the deceased, represented sovereign.…”
mentioning
confidence: 99%
“…Mark Rankin has explored the mechanisms of offering counsel through these two Jacobean plays, and has observed that both Rowley and Shakespeare represented Henry VIII as 'a dynastic predecessor to Stuart rule'. 17 Shakespeare and Rowley framed this character's actions and utterances so as to appeal to the 'interests and agendas' of both James I and his son and heir Henry Frederick. 18 The performance of kingship onstage as a means of offering counsel or seeking royal favour has been extensively studied, 19 and in the context of Jacobean plays on early Tudor history any dramatic representation of the current monarch's predecessors is reflective of the current monarch rather than of the deceased, represented sovereign.…”
mentioning
confidence: 99%